Ceramic tile adhesive and preparation method thereof
By using vinyl chloride copolymer latex powder in ceramic tile glue and other components in synergistically, the problem of insufficient water resistance of existing ceramic tile glue in high humidity and high chemical corrosion environments is solved, and the effects of high water resistance, corrosion resistance, good adhesion and low temperature flexibility are achieved.
Patent Information
- Application Number
- CN202411857215.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-18
AI Technical Summary
The existing ceramic tile glue has insufficient water resistance in high humidity and high chemical corrosion environments, which is prone to fall off, and has insufficient flexibility and adhesion, resulting in poor adhesion effect.
Vinyl chloride copolymer latex powder is used as the main component, combined with cement, quartz sand, calcium formate, cellulose ether and other components, and the water resistance and corrosion resistance of ceramic tile glue are improved through synergistic effects, and good adhesion and low-temperature flexibility are maintained.
It realizes high water resistance and corrosion resistance of ceramic tile glue, maintains good adhesion and low temperature flexibility, reduces dependence on hydrophobic compounds or hydrophobic agents, has simple formula and low cost, and has antibacterial and sterilization properties.
Smart Images

Figure 6UOJK3DTCKTR5SWN6USQUATURNYEIBDOOSHS8OPC 
Figure IPYBYKI1FMIFXI4PSBD1AYXU48ZSE69MX1VSKZF3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a tile adhesive and a preparation method thereof. Background Art
[0002] Ceramic tile is one of the most widely used materials in the field of building decoration. Tile adhesive is a kind of construction adhesive used to stick ceramic tiles, tiles, floor tiles and other decorative materials. It is also called tile adhesive, bonding agent or adhesive mud. It is mainly composed of cement, sand, cellulose ether, latex powder and other additives. It has strong adhesion and anti-falling performance, and can be used for sticking various floor and wall tiles. However, ceramic tiles often have hollow drums and fall off. Due to the different thermal expansion coefficients of different ceramic tiles, relative displacement will occur over time. If the flexibility of the ceramic tile adhesive is not good, the bonding effect will be poor.
[0003] Conventional tile adhesives on the market have poor water resistance. When used in humid places such as bathrooms, kitchens and building exterior walls, a waterproof layer must be made before tiling, which is costly and troublesome. Especially in long-term water-immersion environments such as bathtubs and reservoirs, or in high humidity and high chemical corrosion environments, due to its own insufficient water resistance, general tile adhesives will lose their bonding effect in a short period of time and easily fall off. First, it affects the appearance, and second, the repair requires manpower and material resources. Therefore, the market urgently needs a tile adhesive with high adhesion, good flexibility and high water resistance. Summary of the invention
[0004] In order to solve the problem that the prior art cannot provide a tile adhesive with high adhesion, good flexibility and high water resistance, the present invention discloses a tile adhesive. Through the synergistic effect of vinyl chloride copolymer latex powder and various components, the prepared tile adhesive has excellent water resistance and corrosion resistance, and maintains good adhesion and low-temperature flexibility.
[0005] The technical solution adopted by the present invention to solve its technical problem is: A tile adhesive, comprising the following components in parts by weight: 20-40 parts of cement; 40-70 parts of quartz sand; Calcium formate 2-6 parts; Cellulose ether 0.1-1 part; 0.5-5 parts of latex powder.
[0006] Optionally, the cement is selected from at least one of silicate cement, fly ash silicate cement and composite silicate cement.
[0007] Optionally, the particle size of the quartz sand is 40-100 mesh.
[0008] Optionally, the content of calcium formate is ≥98%.
[0009] Optionally, the cellulase is selected from at least one of hydroxymethyl ethyl cellulose ether, hydroxyethyl cellulose ether and hydroxypropyl methyl cellulose ether.
[0010] Optionally, the latex powder is vinyl chloride copolymer latex powder.
[0011] Optionally, the vinyl chloride-based copolymer latex powder is selected from at least one of vinyl chloride-ethylene-vinyl acetate ternary copolymer latex powder, vinyl chloride-vinyl acetate copolymer latex powder, vinyl chloride-vinyl acetate-versatate vinyl copolymer latex powder and vinyl chloride-vinyl acetate-butyl acrylate copolymer latex powder.
[0012] Another object of the present invention is to provide a method for preparing the tile adhesive as described above, comprising the following steps: adding cement, quartz sand, calcium formate, cellulose ether, and latex powder into a stirring device according to the formula amount, stirring evenly, and obtaining the tile adhesive.
[0013] The present invention has the following beneficial effects: The tile adhesive provided by the present invention achieves significant improvement in performance through the synergistic effect of vinyl chloride copolymer latex powder and various components. This is mainly because vinyl chloride has excellent water resistance and corrosion resistance, and ethylene and vinyl acetate can provide good flexibility and adhesion, especially in low temperature environment, its flexibility is particularly outstanding, so that the prepared tile adhesive has excellent water resistance and corrosion resistance, and maintains good adhesion and low temperature flexibility. In addition, due to the addition of vinyl chloride copolymer latex powder, the tile adhesive of the present invention can achieve excellent water resistance without adding hydrophobic compounds or water repellents, and the formula is simpler and the cost is lower; at the same time, the chlorine element in the tile adhesive of the present invention also gives it certain antibacterial and bactericidal properties, making it more environmentally friendly. DETAILED DESCRIPTION
[0014] The present invention is now further described in detail. The embodiments described below are exemplary and intended to be used to explain the present invention, but cannot be understood as limiting the present invention. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0015] In order to solve the problem that the prior art cannot provide a tile adhesive with high bonding strength, good flexibility and high water resistance, the present invention provides a tile adhesive, which comprises the following components in parts by weight: 20-40 parts of cement; 40-70 parts of quartz sand; Calcium formate 2-6 parts; Cellulose ether 0.1-1 part; 0.5-5 parts of latex powder.
[0016] The tile adhesive provided by the present invention achieves significant improvement in performance through the synergistic effect of vinyl chloride copolymer latex powder and various components. This is mainly because vinyl chloride has excellent water resistance and corrosion resistance, and ethylene and vinyl acetate can provide good flexibility and adhesion, especially in low temperature environment, its flexibility is particularly outstanding, so that the prepared tile adhesive has excellent water resistance and corrosion resistance, and maintains good adhesion and low temperature flexibility. In addition, due to the addition of vinyl chloride copolymer latex powder, the tile adhesive of the present invention can achieve excellent water resistance without adding hydrophobic compounds or water repellents, and the formula is simpler and the cost is lower; at the same time, the chlorine element in the tile adhesive of the present invention also gives it certain antibacterial and bactericidal properties, making it more environmentally friendly.
[0017] Specifically, the preferred cement of the present invention is at least one selected from silicate cement, fly ash silicate cement and composite silicate cement.
[0018] The preferred particle size of the quartz sand in the present invention is 40-100 meshes, which helps to increase the strength and hardness of the tile adhesive and improve the fluidity and durability of the tile adhesive.
[0019] The present invention preferably has a calcium formate content of ≥98%; it can significantly improve the early strength of the tile adhesive, shorten the setting time, and is particularly suitable for construction in winter or under low temperature and humid conditions.
[0020] The preferred cellulose ether of the present invention is at least one selected from the group consisting of hydroxymethyl ethyl cellulose ether, hydroxyethyl cellulose ether and hydroxypropyl methyl cellulose ether.
[0021] The preferred latex powder of the present invention is vinyl chloride copolymer latex powder; The present invention preferably provides a method for preparing the above-mentioned vinyl chloride copolymer latex powder, comprising the following steps: S1: Take 10 parts of polyvinyl alcohol and dissolve it in deionized water, raise the temperature to 80-90°C, and after it is completely dissolved, obtain a polyvinyl alcohol aqueous solution, and maintain the temperature at 70±1°C for later use; S2: Dissolve 5 parts of polyvinyl alcohol in deionized water, raise the temperature to 80-90°C, and after it is completely dissolved, cool it to 45°C, add 40 parts of vinyl chloride, 30 parts of vinyl acetate, 10 parts of acrylate, 0.2 parts of initiator and 0.2 parts of chain transfer agent, and stir until it is completely dissolved to obtain a mixed solution; S3: Take 1 / 5 of the above mixed solution and mix it with the polyvinyl alcohol aqueous solution, keep the temperature at 70±1°C, start the reaction, and then add the remaining 4 / 5 of the mixed solution in succession to continue the reaction; S4: After the reaction is completed, the temperature is lowered to below 40°C, vacuum is drawn, unreacted vinyl chloride is condensed and recovered, the vacuum pump is stopped, the material is discharged, filtered, and packaged to obtain vinyl chloride copolymer emulsion.
[0022] S5: spray-drying the vinyl chloride based copolymer latex or the vinyl chloride based copolymer latex and other latexes at a mass ratio of 1:3 to obtain vinyl chloride based copolymer latex powder.
[0023] Specifically, in the present invention, it is preferred that the other emulsion is at least one selected from vinyl acetate-ethylene copolymer emulsion, vinyl acetate-propylene emulsion and acrylic emulsion.
[0024] Furthermore, the present invention preferably uses at least one of vinyl chloride-based copolymer latex powder selected from vinyl chloride-ethylene-vinyl acetate ternary copolymer latex powder, vinyl chloride-vinyl acetate copolymer latex powder, vinyl chloride-vinyl acetate-versatate vinyl copolymer latex powder and vinyl chloride-vinyl acetate-butyl acrylate copolymer latex powder.
[0025] Another object of the present invention is to provide a method for preparing the tile adhesive as described above, comprising the following steps: adding cement, quartz sand, calcium formate, cellulose ether, and latex powder into a stirring device according to the formula amount, stirring for 0.5-0.6 hours to make it uniform, and obtaining the tile adhesive.
[0026] The preparation method of the tile adhesive provided by the present invention is simple, the preparation process is easy to operate, the construction is convenient, and it is suitable for large-scale production, and can ensure the consistency and reliability of product quality; the tile adhesive prepared by this method not only meets the market demand for high-performance tile adhesive, but also its environmental protection characteristics are also in line with the sustainable development trend of the modern construction industry.
[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below.
[0028] Unless otherwise specified, the content of calcium formate in each embodiment of the present invention and the comparative example is 98%; EVA latex powder was purchased from Shijiazhuang Jiantu New Material Technology Co., Ltd.; acrylic latex powder was purchased from Shanghai Shenye Industrial Co., Ltd.; vinyl acetate-versatate copolymer latex powder was purchased from Shanghai Shunshui Chemical Co., Ltd.
[0029] The amounts of materials used in the various embodiments and comparative examples are all measured in parts by weight.
[0030] This embodiment provides a tile adhesive, which includes the following components in parts by weight: 30 parts of cement; 65 parts of quartz sand; 2 parts of 98% calcium formate; 0.5 parts of cellulose ether; 2.5 parts of latex powder.
[0031] The preparation method of the tile adhesive comprises the following steps: adding cement, quartz sand, calcium formate, cellulose ether and latex powder into a stirring device according to the formula amount, stirring evenly, and obtaining the tile adhesive.
[0032] Specifically, the cement is silicate cement, the quartz sand particle size is 40 meshes, the cellulose ether is hydroxymethyl ethyl cellulose ether, and the latex powder is vinyl chloride-ethylene-vinyl acetate ternary copolymer latex powder; and the stirring time is 0.5h.
[0033] This embodiment provides a tile adhesive, which includes the following components in parts by weight: 20 parts of cement; 70 parts of quartz sand; 6 parts of 98% calcium formate; 1 part of cellulose ether; 3 parts of latex powder.
[0034] The preparation method of the tile adhesive comprises the following steps: adding cement, quartz sand, calcium formate, cellulose ether and latex powder into a stirring device according to the formula amount, stirring evenly, and obtaining the tile adhesive.
[0035] Specifically, the cement is composite silicate cement, the quartz sand particle size is 50 mesh, the cellulose ether is hydroxypropyl ethylmethyl cellulose ether, the latex powder is 2 parts of vinyl chloride-ethylene-vinyl acetate ternary copolymer latex powder and 1 part of vinyl chloride-vinyl acetate copolymer latex powder; the stirring time is 0.5h.
[0036] This embodiment provides a tile adhesive, which includes the following components in parts by weight: 40 parts of cement; 55 parts of quartz sand; 3 parts of 98% calcium formate; 0.5 parts of cellulose ether; 1.5 parts of latex powder.
[0037] The preparation method of the tile adhesive comprises the following steps: adding cement, quartz sand, calcium formate, cellulose ether and latex powder into a stirring device according to the formula amount, stirring evenly, and obtaining the tile adhesive.
[0038] Specifically, the cement is silicate cement, the quartz sand particle size is 70 meshes, the cellulose ether is hydroxymethyl ethyl cellulose ether, and the latex powder is vinyl chloride-vinyl acetate-butyl acrylate copolymer latex powder; and the stirring time is 0.5h.
[0039] This embodiment provides a tile adhesive, which includes the following components in parts by weight: 25 parts of cement; 40 parts of quartz sand; 4 parts of 98% calcium formate; 0.1 part of cellulose ether; 5 parts of latex powder.
[0040] The preparation method of the tile adhesive comprises the following steps: adding cement, quartz sand, calcium formate, cellulose ether and latex powder into a stirring device according to the formula amount, stirring evenly, and obtaining the tile adhesive.
[0041] Specifically, the cement is fly ash silicate cement, the quartz sand particle size is 100 mesh, the cellulose ether is hydroxyethyl cellulose ether, the latex powder is 2 parts of vinyl chloride-vinyl acetate-versatate copolymer latex powder and 3 parts of vinyl chloride-vinyl acetate-butyl acrylate copolymer latex powder; the stirring time is 0.6h.
[0042] The difference between Comparative Example 1 and Example 1 is that the latex powder added is EVA latex powder.
[0043] The difference between Comparative Example 2 and Example 1 is that the latex powder added is acrylic latex powder.
[0044] The difference between Comparative Example 3 and Example 1 is that the latex powder added is vinyl acetate-versatate copolymer latex powder.
[0045] According to the formula amount, the performance of the tile adhesive prepared in each embodiment of the present invention and the comparative example was tested, and the specific test process is as follows: 1. The tile adhesive prepared in each embodiment of the present invention and the comparative example and water were added to a stirring device at a mass ratio of 5:1, and stirred for 5 minutes to obtain a mixture; after the mixture was formed, it was cured for 7 days under ambient temperature conditions of 25° C. and 80% humidity to obtain the tile adhesive to be tested.
[0046] 2. Water-proof pressure test: The test method is based on JGJ / T70-2009 standard. The water-proof pressure test results are shown in Table 1.
[0047] 3. Bond strength test: The test method is in accordance with JC / T907-2018 standard. The tensile bond strength test results are shown in Table 2.
[0048] The results of the anti-seepage pressure test are shown in Table 1: It can be seen from Table 1 that the water permeability pressure of the tile adhesive with high water resistance prepared by the present invention is significantly higher than that of the comparative example, and the anti-permeability performance is effectively improved, indicating that the tile adhesive prepared by the present invention has excellent water resistance.
[0049] The tensile bond strength test results are shown in Table 2: It can be seen from Table 2 that the tile adhesive prepared by the present invention has high water resistance, and still maintains a relatively high tensile bonding strength after being treated with water immersion, heat resistance, freeze-thaw cycles and alkali resistance, which is greatly improved compared with the comparative example.
[0050] The difference between Comparative Example 1 and Example 1 is that the latex powder added is EVA latex powder, and the tensile bonding strength of the obtained tile adhesive is significantly reduced after water immersion, heat resistance, freeze-thaw cycle and alkali resistance treatment, which is due to the addition of chlorine-containing latex powder with excellent water resistance and corrosion resistance.
[0051] The difference between Comparative Example 2 and Example 1 is that the latex powder added is acrylic latex powder, and although the water resistance of the obtained tile adhesive is worse than that of VAE latex powder, it is still not as good as that of vinyl chloride latex powder.
[0052] The difference between Comparative Example 3 and Example 1 is that the latex powder added is vinyl acetate-versatate copolymer latex powder, and the obtained tile adhesive has better water resistance than VAE latex powder, but the water resistance and anti-corrosion effect of the tile adhesive prepared with vinyl chloride latex powder are still far ahead.
[0053] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A tile adhesive, characterized in that: According to parts by weight, it includes the following components: 20-40 parts of cement; 40-70 parts of quartz sand; Calcium formate 2-6 parts; Cellulose ether 0.1-1 part; 0.5-5 parts of latex powder.
2. The tile adhesive according to claim 1, characterized in that: The cement is selected from at least one of silicate cement, fly ash silicate cement and composite silicate cement.
3. The tile adhesive according to claim 1, characterized in that: The particle size of the quartz sand is 40-100 meshes.
4. The tile adhesive according to claim 1, characterized in that: The content of calcium formate is ≥98%.
5. The tile adhesive according to claim 1, characterized in that: The cellulose ether is selected from at least one of hydroxymethyl ethyl cellulose ether, hydroxyethyl cellulose ether and hydroxypropyl methyl cellulose ether.
6. The tile adhesive according to claim 1, characterized in that: The latex powder is vinyl chloride copolymer latex powder.
7. The tile adhesive according to claim 6, characterized in that: The vinyl chloride based copolymer latex powder is selected from at least one of vinyl chloride-ethylene-vinyl acetate ternary copolymer latex powder, vinyl chloride-vinyl acetate copolymer latex powder, vinyl chloride-vinyl acetate-versatate vinyl copolymer latex powder and vinyl chloride-vinyl acetate-butyl acrylate copolymer latex powder.
8. A method for preparing the tile adhesive according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: adding cement, quartz sand, calcium formate, cellulose ether and latex powder into a stirring device according to the formula amount, stirring evenly and obtaining tile adhesive.
Citation Information
Cited By
Weather-resistant multifunctional ceramic tile back adhesive and preparation method thereof
CN121379373A